2020
DOI: 10.29103/jmpe.v1i2.2214
|View full text |Cite
|
Sign up to set email alerts
|

STUDENTS UNDERSTANDING OF SAVINGS PRODUCTS AND SERVICE QUALITY OF BANK TOWARDS THE SAVING INTEREST IN ISLAMIC BANK religiosity as moderating variable (Studies of the student of Islamic Banking Department UIN Ar-Raniry in 2015 Entrance Year)

Abstract: The aim of this study is to see the impact of student understanding of the bank's products and services of Islamic banks on the interest of saving by adding religiosity as a moderating variable. The study uses purposive sampling to select 70 respondents. The study employs the MRA (Moderated Regression Analysis) to analyze the data. The results showed that the students' understanding of savings products have a significant effect on the interests of saving. While the quality of service has no significant effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In addition, study on bank asset securitization towards impact of RELG by Abdelsalam et al (2021) revealed that bank in countries with high RELG adherence are likely to have Islamic banks engage in highly monitored asset securitization models to improve portfolio diversification, financial performance and regulatory compliance. In relation to this, Lianda et al (2020) research proves that RELG significantly associated with the quality of bank service.…”
Section: Literature Review 21 Theoretical Backgroundmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, study on bank asset securitization towards impact of RELG by Abdelsalam et al (2021) revealed that bank in countries with high RELG adherence are likely to have Islamic banks engage in highly monitored asset securitization models to improve portfolio diversification, financial performance and regulatory compliance. In relation to this, Lianda et al (2020) research proves that RELG significantly associated with the quality of bank service.…”
Section: Literature Review 21 Theoretical Backgroundmentioning
confidence: 67%
“…Moreover, the effect of RELG on the withdrawal of non-Muslims from Islamic banking can vary between individuals and communities (Abdelsalam et al , 2021; Lianda et al , 2020). Using PPM theory, Rhoudri and Benazzou (2022) examine Moroccan profit-sharing investment account holders’ deposit withdrawal intentions, used structural equation modelling to evaluate variables in a quantitative survey of 166 depositors from five Moroccan banks.…”
Section: Literature Reviewmentioning
confidence: 99%